Move everything to old
[lambda.git] / hints / assignment_4_hint_3_alternate_1.mdwn
diff --git a/hints/assignment_4_hint_3_alternate_1.mdwn b/hints/assignment_4_hint_3_alternate_1.mdwn
deleted file mode 100644 (file)
index f75bad0..0000000
+++ /dev/null
@@ -1,58 +0,0 @@
-Alternate strategy for Y1, Y2
-
-*      This is (in effect) the strategy used by OCaml. The mutually recursive:
-
-               let rec
-                       f x = A  ; A may refer to f or g
-               and
-                       g y = B  ; B may refer to f or g
-               in
-                       C
-
-       is implemented using regular, non-mutual recursion, like this (`u` is a variable not occurring free in `A`, `B`, or `C`):
-
-               let rec  u g x = (let f = u g in A)  in
-               let rec    g y = (let f = u g in B)  in
-               let                   f = u g        in
-               C
-
-       or, expanded into the form we've been working with:
-
-               let u =    Y (\u g. (\f x. A) (u g))  in
-               let g =    Y (  \g. (\f y. B) (u g))  in
-               let f =                        u g    in
-               C
-
-       We could abstract Y1 and Y2 combinators from this as follows:
-
-               let Yu = \ff.    Y (\u g. ff ( u      g        ) g)  in
-               let Y2 = \ff gg. Y (  \g. gg (Yu ff   g        ) g)  in
-               let Y1 = \ff gg.             (Yu ff) (Y2 ff gg)      in
-               let f  = Y1 (\f g. A) (\f g. B)  in
-               let g  = Y2 (\f g. A) (\f g. B)  in
-               C
-
-
-*      Here's the same strategy extended to three mutually-recursive functions. `f`, `g` and `h`:
-
-               let v = Y (\v g h.      (\f x. A) (v g h)) in
-               let w = Y (  \w h. (\g. (\f y. B) (v g h)) (w h)) in
-               let h = Y (    \h. (\g. (\f z. C) (v g h)) (w h)) in
-               let g =                                     w h in
-               let f =                            v g h in
-               D
-
-       <!--
-       Or in Y1of3, Y2of3, Y3of3 form:
-
-               let Yv    = \ff.       Y (\v g h.      ff ( v    g h) g h)                in
-               let Yw    = \ff gg.    Y (  \w h. (\g. gg (Yv ff g h) g h) ( w       h))  in
-               let Y3of3 = \ff gg hh. Y (    \h. (\g. hh (Yv ff g h) g h) (Yw ff gg h))  in
-               let Y2of3 = \ff gg hh.                                      Yw ff gg (Y3of3 ff gg hh)  in
-               let Y1of3 = \ff gg hh.                     Yv ff (Y2of3 ff gg hh) (Y3of3 ff gg hh)     in
-               let f = Y1of3 (\f g h. A) (\f g h. B) (\f g h. C)  in
-               let g = Y2of3 (\f g h. A) (\f g h. B) (\f g h. C)  in
-               let h = Y3of3 (\f g h. A) (\f g h. B) (\f g h. C)  in
-               D
-       -->
-